Italy : Financial Sector Assessment Program-Technical Note-Systemic Risk Analysis and Stress Testing of the Banking and Corporate Sectors. (IMF Staff Country Reports; Country Report ;, 2020)
The Financial Sector Assessment Program (FSAP) took place against the backdrop of an ongoing recovery of the financial system. Since the global financial crisis (GFC), financial regulation has been substantially enhanced by the implementation of euro area-wide (EA-wide) regulatory and supervisory frameworks. Furthermore, the Italian authorities have implemented important measures that improved governance, facilitated capitalization, raised prudential requirements, and improved asset quality. In response, Italian banks have made substantial progress tackling legacy non-performing loans (NPLs) and improving solvency ratios.